P1-S2.55 High incidence of HIV and low HIV prevention coverage among men who have sex with men in Managua, Nicaragua. (10th July 2011) - Hernandez, F; Arambú, N; Alvarez, B; Romero, L; GoinsEBeteta, J; Paz-Bailey, G; Morales, S
Abstract : Background: High rates of HIV and sexually transmitted infections (STI) are found in men who have sex with men (MSM) in Nicaragua. This study investigated HIV, STI, and risk behaviours in MSM. Methods: From 9/2009 to 2/2010, MSM 18 years or older who gave written informed consent and reported having anal sex with a man in the last year were recruited using respondent-driven sampling in Managua. The survey process included audio computer assisted survey instruments (ACASI) and face-to-face interviews followed by STI counselling and specimen collection for HIV (Uni-Gold Recombigen®, Determine®, HIV Elisa and Western Blot), HSV-2 (Elisa IgG Focus® Technology, Inc), and syphilis testing (RPR/TPPA). Gonorrhoea, Chlamydia, Mycoplasma genitalium and Trichomonas were tested by PCR. The BED IgG capture enzyme immunoassay was applied to HIV positive specimens to detect recently-acquired HIV infections, used to estimate HIV incidence. Population proportions and 95% CIs were calculated and adjusted for RDS-sampling weights. Incidence estimates were adjusted using a locally-established false-recent rate for the assay. Data analyses were conducted in STATA 9.0 and RDSAT 6.1. Results: Respondents self-identified as bisexual (50%), gay (41%), heterosexual (1%) or transgender (8%). In the last year, 34.5% had one or more stable partner and 66% had occasional partners. Sex with women during lifetime was reported by 66% and 40% in the last year. Consistent condom use (last 30 days) was reported at 31% with stable male partner, 12%, with stable female partner, 38% with occasional partner, and 38% with clients. Condom use in last sex was 62%. Overall, 36% had received peer-driven outreach for HIV prevention and 64% had been tested for HIV in the last year. HIV prevalence in Managua was determined to be 7.5% (CI 4.5% to 11%), incidence 2.9% (CI 0.2% to 5.6%). Herpes simplex 2 was the most prevalent STI at 39.9% (CI 34.4% to 46%) see Abstract P1-S2.55 Table 1 . Conclusions: The 2003 Multicentric Study found a similar prevalence in Managua among MSM at 9.4% (CI 5.3% to 14.8%). Condom use is low with all types of partners, but lowest with female partners. The population's high HIV incidence, coupled with low access to education, underlines the urgency of enhancing prevention activities among this population. Stronger strategies are needed to ensure that prevention, care, and treatment interventions reach this population.